The role of Kingella kingae in pre-school aged children with bone and joint infections. Issue 3 (September 2021) - Olijve, Laudi; Amarasena, Lahiru; Best, Emma; Blyth, Christopher; van den Boom, Mirjam; Bowen, Asha; Bryant, Penelope A.; Buttery, Jim; Dobinson, Hazel C.; Davis, Joshua; Francis, Joshua; Goldsmith, Heidi; et al.
Highlights: Osteoarticular infections in children under 5 years old are often culture negative. The peak incidence of osteoarticular infections was between 12 and 24 months of age. In this age group K. kingae was the most prevalent pathogen. Many culture-negative cases may be missed cases of Kingella infection. Routine PCR testing of samples is likely to increase Kingella detection rates. Abstract: Objectives: The Pre-school Osteoarticular Infection (POI) study aimed to describe the burden of disease, epidemiology, microbiology and treatment of acute osteoarticular infections (OAI) and the role of Kingella kingae in these infections. Methods: Information about children 3–60 months of age who were hospitalized with an OAI to 11 different hospitals across Australia and New Zealand between January 2012 and December 2016 was collected retrospectively. Results: A total of 907 cases (73%) were included. Blood cultures grew a likely pathogen in only 18% (140/781). The peak age of presentation was 12 to 24 months (466/907, 51%) and Kingella kingae was the most frequently detected microorganism in this age group (60/466, 13%). In the majority of cases, no microorganism was detected (517/907, 57%). Addition of PCR to culture increased detection rates of K. kingae. However, PCR was performed infrequently (63/907, 7%). Conclusions: This large multi-national study highlights the need for more widespread use of molecular diagnostic techniques for accurate microbiological diagnosis of OAI in pre-school aged children. The data from this study supports the hypothesis that a substantial proportion of pre-school aged children with OAI and no organism identified may in fact have undiagnosed K. kingae infection. Improved detection of Kingella cases is likely to reduce the average length of antimicrobial treatment. Graphical abstract: Image, graphical abstract